Bacillus subtilis biofilm matrix components target seed oil bodies to promote growth and anti-fungal resistance in melon - Berlanga-Clavero, María Victoria; Molina-Santiago, c; Caraballo-Rodríguez, Andrés Mauricio; Petras, Daniel; Diaz-Martínez, Luis; Pérez, Alejandro; De-Vicente-Moreno, Antonio; Carrión, Víctor; Dorrestein, Pieter; Romero, Diego (Springer Nature, 2022)
Beneficial microorganisms are used to stimulate the germination of seeds; however, their growth-promoting mechanisms remain largely unexplored. Bacillus subtilis is commonly found in association with different plant organs, providing protection against pathogens or stimulating plant growth. We report that application of B. subtilis to melon seeds results in genetic and physiological responses in seeds that alter the metabolic and developmental status in 5-d and 1-month-old plants upon germination. We analysed mutants in different components of the extracellular matrix of B. subtilis biofilms in interaction with seeds and found cooperation in bacterial colonization of seed storage tissues and growth promotion. Combining confocal microscopy with fluorogenic probes, we found that two specific components of the extracellular matrix, amyloid protein TasA and fengycin, differentially increased the concentrations of reactive oxygen species inside seeds. Further, using electron and fluorescence microscopy and metabolomics, we showed that both TasA and fengycin targeted the oil bodies in the seed endosperm, resulting in specific changes in lipid metabolism and accumulation of glutathione-related molecules. In turn, this results in two different plant growth developmental programmes: TasA and fengycin stimulate the development of radicles, and fengycin alone stimulate the growth of adult plants and resistance in the phylloplane to the fungus Botrytis cinerea. Understanding mechanisms of bacterial growth promotion will enable the design of bespoke growth promotion strains.
Keywords: Bacillus (Bacteria); Bacillus; Plants; Biofilm